Challenges Faced by Teachers in Implementing the Merdeka Curriculum Assessment Model - Manda Putri Berutu; Izza Syafinas Nurafitha Hasibuan; Aurel Putri Azahra; Michael Josep Sirait; Maulana Ramadhan Silalahi; Syarifah Nurmasyittah; Ammar Zhafran Ryanto (Historia, 2027)
Kurikulum Merdeka is an education policy that transforms learning and assessment in schools by emphasizing learning processes, competencies, and character development. Teachers are required to implement diagnostic, formative, and summative assessments but still face challenges such as limited understanding, training, time constraints, administrative burdens, and difficulty assessing non-cognitive aspects. This study aims to analyze teachers' role in assessment under Kurikulum Merdeka, the challenges encountered, and efforts to address them using a descriptive qualitative literature study approach. Data were collected from journals, scientific articles, and relevant literature, then analyzed to examine assessment implementation. Results show that implementation still faces obstacles; therefore continuous training, simplified administration, technology use, and support from schools and government are needed to optimize assessment practices. Thus, teachers play a crucial role in ensuring effective assessment that supports student competency and character development through continuous improvement, collaboration, and educational policy support in school environments implementation and practice process.